An evaluation of a professional learning network for computer science teachers. Issue 1 (2nd January 2017) - Cutts, Quintin; Robertson, Judy; Donaldson, Peter; O'Donnell, Laurie
Abstract: This paper describes and evaluates aspects of a professional development programme for existing CS teachers in secondary schools (PLAN C) which was designed to support teachers at a time of substantial curricular change. The paper's particular focus is on the formation of a teacher professional development network across several hundred teachers and a wide geographical area. Evidence from a series of observations and teacher surveys over a two-year period is analysed with respect to the project's programme theory in order to illustrate not only whether it worked as intended, by why . Results indicate that the PLAN C design has been successful in increasing teachers' professional confidence and appears to have catalysed powerful change in attitudes to learning. Presentation of challenging pedagogical content knowledge and conceptual frameworks, high-quality teacher-led professional dialogue, along with the space for reflection and classroom trials, triggered examination of the teachers' own current practices.